2020
DOI: 10.1002/ecs2.3178
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of grassland metacommunities is regulated more by community functional traits than species diversity

Abstract: Temporal stability in aboveground net primary productivity (ANPP) is influenced by several attributes of plant communities. Identifying the primary regulators of stability and their roles across spatial scales is of both practical and theoretical importance. We assessed effects of species diversity (local or alpha diversity and species dissimilarity between local communities) together with spatial differences in two community functional attributes (mean aboveground biomass and community leaf dry matter content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Aboveground biomass per patch in spring (in grams per square meter; assumed equal to early‐season ANP) was calculated as an exponential function of the enhanced vegetation index (EVI) (adjusted r 2 = 0.83, p < 0.0001; Polley, Yang, et al, 2020b). EVIgoodbreak=Ggoodbreak×[]()NIRgoodbreak−Red/()NIRgoodbreak+C1goodbreak×Redgoodbreak−C2goodbreak×Bluegoodbreak+L, where NIR, red, and blue are reflectance in near‐infrared, red, and blue wavelengths, respectively; L is an adjustment for canopy background; G is a gain factor; and coefficients C 1 and C 2 correct for the influence of aerosols ( L = 1, C 1 = 6, C 2 = 7.5, and G = 2.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboveground biomass per patch in spring (in grams per square meter; assumed equal to early‐season ANP) was calculated as an exponential function of the enhanced vegetation index (EVI) (adjusted r 2 = 0.83, p < 0.0001; Polley, Yang, et al, 2020b). EVIgoodbreak=Ggoodbreak×[]()NIRgoodbreak−Red/()NIRgoodbreak+C1goodbreak×Redgoodbreak−C2goodbreak×Bluegoodbreak+L, where NIR, red, and blue are reflectance in near‐infrared, red, and blue wavelengths, respectively; L is an adjustment for canopy background; G is a gain factor; and coefficients C 1 and C 2 correct for the influence of aerosols ( L = 1, C 1 = 6, C 2 = 7.5, and G = 2.5).…”
Section: Methodsmentioning
confidence: 99%
“…Aboveground biomass per patch in spring (in grams per square meter; assumed equal to early-season ANP) was calculated as an exponential function of the enhanced vegetation index (EVI) (adjusted r 2 = 0.83, p < 0.0001; Polley, Yang, et al, 2020b).…”
Section: Field Measurements and Variable Calculationmentioning
confidence: 99%
“…Resilience, resistance and restoration are the main elements in determining whether an ecosystem is stable [ 33 ]. The study of the role of biodiversity, species diversity and functional traits on stability has been the focus of ecosystem research [ 34 , 35 , 36 , 37 ], and they are influenced by multiple factors on multiple scales [ 38 ]. It has been shown that extreme weather and irrational human activities are the main drivers of structural changes in grassland ecosystems [ 39 ], which indirectly alter ecosystem stability, increase the overall vulnerability of grassland ecosystems and reduce their capacity to provide ecosystem services [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing observations might allow this knowledge gap to be closed (Franklin et al, 2017; Polley et al, 2020; Rocchini et al, 2021). Remote Earth observation products have become widely available and allow the assessment of ecosystem functionality and biodiversity (Lausch et al, 2016; Schmidtlein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%